(untitled) (Research, Society and Development, 2020)
Fruits and vegetables are widely processed, and during its processing, co-products are often discarded. Some co-products, such as peels, have a rich composition and could be used. However, the high perishability, due to high moisture content, limits this use. The reduction of moisture, achieved by drying, is an alternative to use these co-products. Flours, made from pineapple (Ananas comosus), banana (Musa sp.), lychee (Litchi chinensis) and papaya (Carica papaya) peels, through drying process, were evaluated for particle size distribution, water activity, hydrogenionic potential, titratable acidity, total soluble solids, solubility in water and in milk and water, milk and oil absorption, in order to characterize them and suggest potential applications in food products. Water activity (0.21 to 0.38) and pH (3.58 to 5.84) values were favorable for the preservation of flours, which also showed better solubility in water (17.57 to 53.52%) than in milk (4.46 to 11.22%), as well as a higher water uptake (2.16 to 6.35 g g-1) and milk (3.19 to 6.61 g g-1) compared to oil absorption (1.09 to 1.74 g g-1). These results indicated good potential for use in food processing, especially in instant products, meat and bakery, to develop new products or replace ingredients, representing an alternative to the use of co-products.